Does common analyst coverage improve suppliers' investment efficiency? - Ceng Zeng; Song Tang (China Journal of Accounting Studies (CJAS), 2023)
This study examines the effect of common analysts covering both suppliers and their major customers on suppliers' investment efficiency. Using a sample of A-share listed firms in China from 2007 to 2018, we find that suppliers with common analyst coverage exhibit higher investment efficiency. This effect is stronger when suppliers have greater demand for obtaining customer information from common analysts, for example, when suppliers have shorter relationships with and are smaller than their customers, and when their customers have more fluctuating earnings and poorer accounting information quality. It is also stronger when common analysts possess a distinct information advantage about customers, for example, when they have relatively higher customer industry specialisation, more information about customers' competitors, more experience, and are star analysts. Taken together, our results suggest that suppliers can obtain prospective information about their customers from common analysts, which facilitates suppliers' efficient investment.
Keywords: 650; Common analyst; investmentefficiency; informationasymmetry; supplier; customer